Повышение эффективности процесса прерывистого шлифования - Якимов, А. А.; Бовнегра, Л. В.; Шихирева, Ю. В.; Павлышко, Е. Г.; Королькова, М. В. (Национальный технический университет "Харьковский политехнический институт", 2019)
Высокая теплонапряженность процесса шлифования вызывает снижение показателей качества поверхностного слоя обрабатываемых деталей. Снизить теплонапряженность можно применением прерывистых шлифовальных кругов. Но работа этих кругов сопровождается периодическим изменением жесткости упругой системы плоскошлифовального станка и, как следствие, возникновением в ней периодических колебаний. Эти колебания способны вызвать в ней появление периодических дефектов — циклических прижогов и волнистости на обрабатываемых поверхностях. В статье выявлены условия ухудшения геометрических и физико-механических параметров качества поверхностни деталей при прерывистом шлифовании и предложены пути их предотвращения. Обоснована целесообразность использования прерывистых кругов с наклонными пазами и кругов со спиральными канавками на рабочих поверхностях.

Grinding is the most common method for machining hardened steel parts. However, due to the high thermal stress of the grinding process, various defects appear on the machined surfaces, significantly reducing the operational reliability of the parts produced. One of the effective ways to improve the quality of the surface layer and the performance of grinding is the use of abrasive tools with a discontinuous working surface. But the incorrect application of these circles often leads to the formation of additional defects on the surfaces being treated — waviness and technical burns. The article reveals the conditions for the deterioration of the geometric and physico-mechanical parameters of the quality of the surface layer of parts in the grinding operation with abrasive wheels with a discontinuous working surface. The ways of improving the quality of the surface layer of parts with intermittent grinding are proposed. It has been established that when grinding with a discontinuous circle with grooves parallel to the tool axis, it is very difficult to prevent the occurrence of grinding defects due to constantly changing processing conditions (changing the parameters of the cutting mode, filling the working surface of the wheel), resulting in the appearance of parametric grinding in the elastic surface grinding machine. On the basis of theoretical and experimental studies, the expediency of using abrasive wheels with spiral grooves or inclined grooves on working surfaces in an operation is determined.
Increase efficiency of interrupted grinding process
Keywords: параметрическая неустойчивость; прерывистый круг; температура шлифования; коэффициент прерывистости; parametric instability; intermittent lap; grinding temperature; discontinuity factor